The 1948 Universal Declaration of Human Rights (UDHR) – Impact on Central and Eastern European Countries - Siradze, Eka; Kurdadze, Irine (The Universal Protection of Human Rights, 2026)
Abstract: This chapter presents a comprehensive overview of the development of the Universal Declaration of Human Rights as the cornerstone of the international bill of rights, its legal nature and its impact on universal and regional human rights treaties, based on the extensive literature, the Travaux Préparatoires and commentaries on the UDHR, as well as resolutions of the United Nations, the Human Rights Committee, etc., decisions of international courts and national reports of states. The study begins with the concept and meaning of the International Bill of Human Rights and then highlights the contribution of the Universal Declaration of Human Rights to the international human rights system – the impact of the Universal Declaration of Human Rights on human rights instruments at the universal and regional levels. Next important matter addressed is the legal nature of the UDHR as a source of international law and its path from soft law to customary law. And finally, implementation of UDHR (which does not establish any judicial or quasi-judicial system to consider claims by individuals or States) is analysed on the basis of both the practice of the HRC and the national reports of the 16 Central and Eastern European countries that underwent the UPR process. Keywords: UDHR, Bill of Rights, Soft Law, HRC, UPR, National reports